Reusable alcohol-resistant antistatic film and preparation method thereof

By using chemical precoats composed of polyvinyl alcohol, isobutyl acetate and ortho-silicate in the antistatic film and the antistatic layer formed by carbon nanotubes, the problem of reducing the antistatic effect of the existing antistatic film when wiping with alcohol is solved, and high alcohol resistance and reusability are achieved.

CN120082083APending Publication Date: 2025-06-03YANGZHOU ALVIN OPTOELECTRONIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510330172.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-20
Publication Date
2025-06-03

AI Technical Summary

Technical Problem

The existing antistatic films have reduced antistatic effect when wiping with alcohol, and most polythiophene coatings are not resistant to alcohol, resulting in poor alcohol resistance of the film.

Method used

The chemical precoat consisting of polyvinyl alcohol, isobutyl acetate and ethyl orthosilicate is used to combine the antistatic layer formed by carbon nanotubes to improve the solvent resistance and hardness of the coating by forming Si-O-C covalent bonds and three-dimensional Si-O-Si crosslinking structure.

Benefits of technology

It achieves the maintenance of antistatic effect in an alcohol environment, improves the alcohol resistance and adhesion of the membrane, and supports the reusability of the membrane, which has high economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005320042850000091
    Figure BDA0005320042850000091
Patent Text Reader

Abstract

The invention relates to the technical field of antistatic materials, and particularly provides a reusable alcohol-resistant antistatic film and a preparation method thereof.The reusable alcohol-resistant antistatic film comprises a base material layer, a chemical pre-coating layer and an antistatic layer, the chemical pre-coating layer and the antistatic layer are sequentially arranged on the base material layer, and the chemical pre-coating layer is composed of polyvinyl alcohol with the molecular weight ranging from 20000 Da to 30000 Da, isobutyl acetate and tetraethoxysilane. A pre-coating system composed of polyvinyl alcohol, isobutyl acetate and tetraethoxysilane is adopted, and the long-standing pain points of poor alcohol resistance, insufficient adhesive force and non-repeated use of the antistatic film are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of antistatic materials, and particularly to a reusable alcohol-resistant antistatic film and a preparation method thereof. Background Art

[0002] Antistatic release films have a wide range of application fields, mainly including electronic products, household appliances, automobiles, medical equipment, etc. Among them, the main application field is the electronic product manufacturing industry. During the production process of electronic products, static electricity may damage sensitive electronic components. The antistatic PET protective film can effectively eliminate or reduce the generation of static electricity, thereby protecting the safety of electronic components. In addition, static electricity may cause dust adsorption, affecting the clarity and performance of optical components. The antistatic PET protective film can be used as a protective layer for optical components to effectively prevent static electricity from adsorbing dust.

[0003] Currently, ordinary antistatic films on the market are prepared by coating a layer of polythiophene coating on the surface of the substrate. Since most polythiophene coatings are not alcohol-resistant, when wiping optical components with alcohol, the antistatic effect of the antistatic PET protective film will also decrease. Summary of the Invention

[0004] In view of this, the present invention provides a reusable alcohol-resistant antistatic film and a preparation method thereof.

[0005] The technical solution of the present invention is realized as follows: The present invention provides a reusable alcohol-resistant antistatic film, which includes a substrate layer, and a chemical pre-coating layer and an antistatic layer sequentially arranged on the substrate layer. The chemical pre-coating layer is composed of polyvinyl alcohol with a molecular weight of 20,000 Da - 30,000 Da, isobutyl acetate, and tetraethyl orthosilicate.

[0006] The hydroxyl groups in the PVA molecular chain endow it with excellent film-forming ability, forming a uniform pre-coating substrate. The hydroxyl groups of PVA and the silanol groups generated by the hydrolysis of tetraethyl orthosilicate under heating conditions condense to form Si - O - C covalent bonds during the curing process, constituting an organic-inorganic hybrid network. At the same time, the silanol groups themselves condense to form a three-dimensional Si - O - Si cross-linked structure, significantly improving the solvent resistance and hardness of the coating. Isobutyl acetate, as a high-boiling solvent, delays the evaporation rate, avoids cracking caused by rapid drying of the coating, and ensures the uniformity of the pre-coating layer.

[0007] In some embodiments, calculated by weight percentage, the chemical pre-coating layer is composed of 75% - 85% of polyvinyl alcohol with a molecular weight of 20,000 Da - 30,000 Da, 10% - 15% of isobutyl acetate, and 5% - 10% of tetraethyl orthosilicate.

[0008] In some embodiments, the antistatic layer is composed of water, isopropyl alcohol, and carbon nanotubes.

[0009] In the coating, carbon nanotubes form a three-dimensional conductive network through physical lap joints. Electrons are rapidly transported through the π-π conjugate structure of the carbon nanotubes, reducing the surface resistance. At the same time, carbon nanotubes have chemical inertness, enabling them to remain stable in an alcohol polar solvent environment and avoiding performance degradation of the polythiophene coating caused by dissolution or swelling. Isopropyl alcohol can reduce the surface tension of water, promote the dispersion of carbon nanotubes, reduce agglomeration, and at the same time, as a co-solvent, isopropyl alcohol can accelerate the volatilization during the curing process.

[0010] In some embodiments, calculated by weight percentage, the antistatic layer is composed of 40%-45% water, 40%-45% isopropyl alcohol, and 10%-20% carbon nanotubes.

[0011] The above mixing ratio of water bath isopropyl alcohol can balance the dispersibility and volatility, ensuring a uniform and defect-free coating.

[0012] In some embodiments, the diameter of the carbon nanotubes is 1-3 nm.

[0013] In some embodiments, the substrate layer is a PET film.

[0014] In some embodiments, the thickness of the substrate layer is 50-75 μm.

[0015] In some embodiments, the thickness of the chemical pre-coating is 3-5 μm.

[0016] In some embodiments, the thickness of the antistatic layer is 0.02-0.03 μm.

[0017] The second aspect of the present invention also provides a method for preparing the above-mentioned reusable alcohol-resistant antistatic film, including the following steps: mixing polyvinyl alcohol and isobutyl acetate according to the ratio, adding tetraethyl orthosilicate during the stirring process and mixing evenly, then coating on the surface of the substrate layer to form a chemical pre-coating, putting it into an oven at 150-160 °C for curing for 10-20 s. Then, mixing water, isopropyl alcohol, and carbon nanotubes according to the ratio, stirring evenly, coating on the surface of the chemical pre-coating to form an antistatic layer, and putting it into an oven at 135-145 °C for curing for 10-20 s to obtain the finished product.

[0018] The present invention has the following beneficial effects compared with the prior art:

[0019] The present invention adopts a pre-coating system composed of polyvinyl alcohol, isobutyl acetate, and tetraethyl orthosilicate, solving the long-existing pain points of poor alcohol resistance, insufficient adhesion, and non-reusability of antistatic films. Compared with the existing antistatic PET protective films, it improves the defect of poor alcohol resistance of the existing polythiophene antistatic. At the same time, the reusable alcohol-resistant antistatic film of the present invention can be reused during the production, transportation, and storage of electronic devices, having higher economic benefits. Detailed implementation manners

[0020] The following will describe the technical solutions in the embodiments of the present invention clearly and completely in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.

[0021] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the technical field to which the embodiments of the present invention belong. If the definitions stated in this part are contrary to or inconsistent with the definitions stated in the patents, patent applications, published patent applications and other publications incorporated herein by reference, the definitions listed in this part shall prevail over the definitions incorporated herein by reference.

[0022] Unless otherwise specified, the methods used in the following embodiments are all conventional methods. The materials, reagents and instruments used, unless otherwise specified, are all conventional materials, reagents and instruments in the art, and those skilled in the art can obtain them through commercial channels.

[0023] When an equivalent, concentration or other value or parameter is expressed as a range, a preferred range or a range defined by a series of upper limit preferred values and lower limit preferred values, it should be understood that all ranges formed by any pairing of any range upper limit or preferred value and any range lower limit or preferred value are specifically disclosed, regardless of whether the ranges are separately disclosed. For example, when the range "1 to 5" is disclosed, the described range should be interpreted as including the ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described herein, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range. In the specification and claims of this application, range limitations can be combined and / or interchanged, and if not otherwise stated, these ranges include all sub-ranges contained therein.

[0024] Example 1

[0025] This example provides a technical solution for an alcohol-resistant and antistatic film, and the substrate layer is a PET film.

[0026] Raw materials for the chemical pre-coating layer: 80% of polyvinyl alcohol with a molecular weight of 25000 Da, 15% of isobutyl acetate, and 5% of tetraethyl orthosilicate;

[0027] Raw materials for the antistatic layer: 40% of water, 40% of isopropyl alcohol, and 20% of carbon nanotubes with a tube diameter of 2 nm.

[0028] Preparation method: Mix polyvinyl alcohol and isobutyl acetate according to the ratio, stir at 60 °C for 2 h until completely dissolved. During the stirring process, add tetraethyl orthosilicate and mix evenly, then coat it on the surface of the substrate layer to form a chemical pre-coating layer, and place it in an oven at 155 °C for curing for 15 s. Then mix water, isopropyl alcohol, and carbon nanotubes according to the ratio, ultrasonically disperse for 30 min, and then evenly coat it on the surface of the chemical pre-coating layer to form an antistatic layer, and place it in an oven at 140 °C for curing for 15 s to obtain the finished product. In the finished product, the thickness of the substrate layer is 50 μm, the thickness of the chemical pre-coating layer is 3 μm, and the thickness of the antistatic layer is 0.02 μm.

[0029] Example 2

[0030] This example provides a technical solution for an alcohol-resistant antistatic film, and the substrate layer is a PET film.

[0031] Raw materials for the chemical pre-coating layer: 85% of polyvinyl alcohol with a molecular weight of 25000 Da, 10% of isobutyl acetate, and 5% of tetraethyl orthosilicate;

[0032] Raw materials for the antistatic layer: 45% of water, 45% of isopropyl alcohol, and 10% of carbon nanotubes with a diameter of 2 nm.

[0033] Preparation method: Mix polyvinyl alcohol and isobutyl acetate according to the ratio. During the stirring process, add tetraethyl orthosilicate and mix evenly, then coat it on the surface of the substrate layer to form a chemical pre-coating layer, and place it in an oven at 155 °C for curing for 15 s. Then mix water, isopropyl alcohol, and carbon nanotubes according to the ratio, ultrasonically disperse for 30 min, and then evenly coat it on the surface of the chemical pre-coating layer to form an antistatic layer, and place it in an oven at 140 °C for curing for 15 s to obtain the finished product. In the finished product, the thickness of the substrate layer is 50 μm, the thickness of the chemical pre-coating layer is 3.5 μm, and the thickness of the antistatic layer is 0.03 μm.

[0034] Example 3

[0035] This example provides a technical solution for an alcohol-resistant antistatic film, and the substrate layer is a PET film.

[0036] Raw materials for the chemical pre-coating layer: 75% of polyvinyl alcohol with a molecular weight of 25000 Da, 15% of isobutyl acetate, and 10% of tetraethyl orthosilicate;

[0037] Raw materials for the antistatic layer: 40% of water, 40% of isopropyl alcohol, and 20% of carbon nanotubes with a diameter of 2 nm.

[0038] Preparation method: Mix polyvinyl alcohol and isobutyl acetate according to the ratio. During stirring, add tetraethyl orthosilicate and mix evenly, then coat it on the surface of the substrate layer to form a chemical pre-coating. Place it in an oven at 160 °C for 20 s to cure. Then mix water, isopropyl alcohol, and carbon nanotubes according to the ratio, ultrasonically disperse for 30 min, and then evenly coat it on the surface of the chemical pre-coating to form an antistatic layer. Place it in an oven at 140 °C for 15 s to cure, and the finished product is obtained. In the finished product, the thickness of the substrate layer is 75 μm, the thickness of the chemical pre-coating is 5 μm, and the thickness of the antistatic layer is 0.02 μm.

[0039] Comparative Example 1

[0040] This comparative example uses an antistatic film without a pre-coating, and the substrate layer is a PET film.

[0041] Antistatic layer raw materials: 40% water, 40% isopropyl alcohol, 20% carbon nanotubes with a diameter of 2 nm.

[0042] Preparation method: Mix water, isopropyl alcohol, and carbon nanotubes according to the ratio, ultrasonically disperse for 30 min, and then evenly coat it on the surface of the substrate layer to form an antistatic layer. Place it in an oven at 140 °C for 15 s to cure, and the finished product is obtained. In the finished product, the thickness of the substrate layer is 50 μm, and the thickness of the antistatic layer is 0.02 μm.

[0043] Comparative Example 2

[0044] This comparative example uses an antistatic film in which the chemical pre-coating does not contain tetraethyl orthosilicate, and the substrate layer is a PET film.

[0045] Chemical pre-coating raw materials: 85% polyvinyl alcohol with a molecular weight of 25000 Da, 15% isobutyl acetate;

[0046] Antistatic layer raw materials: 40% water, 40% isopropyl alcohol, 20% carbon nanotubes with a diameter of 2 nm.

[0047] Preparation method: Mix polyvinyl alcohol and isobutyl acetate according to the ratio, stir and mix evenly, coat it on the surface of the substrate layer to form a chemical pre-coating, place it in an oven at 155 °C for 15 s to cure. Then mix water, isopropyl alcohol, and carbon nanotubes according to the ratio, stir evenly, coat it on the surface of the chemical pre-coating to form an antistatic layer, place it in an oven at 140 °C for 15 s to cure, and the finished product is obtained. In the finished product, the thickness of the substrate layer is 50 μm, the thickness of the chemical pre-coating is 3 μm, and the thickness of the antistatic layer is 0.02 μm.

[0048] Comparative Example 3

[0049] This comparative example provides a technical solution of a polythiophene coating without a chemical pre-coating.

[0050] Antistatic layer raw materials: Polythiophene conductive solution (commercially available PEDOT:PSS, solid content 1.2%).

[0051] Preparation method: The polythiophene conductive solution is evenly coated on the surface of the substrate layer to form an antistatic layer, and then placed in an oven at 120 °C for curing for 30 s to obtain the finished product. In the finished product, the thickness of the substrate layer is 50 μm, and the thickness of the antistatic layer is 0.1 μm.

[0052] Comparative Example 4

[0053] In this comparative example, the technical solution of an alcohol-resistant antistatic film using large-diameter carbon nanotubes is adopted, and the substrate layer is a PET film.

[0054] Chemical pre-coating raw materials: 80% of polyvinyl alcohol with a molecular weight of 25000 Da, 15% of isobutyl acetate, and 5% of tetraethyl orthosilicate;

[0055] Antistatic layer raw materials: 40% of water, 40% of isopropyl alcohol, and 20% of carbon nanotubes with a diameter of 6 nm.

[0056] Preparation method: Polyvinyl alcohol and isobutyl acetate are mixed according to the ratio and stirred at 60 °C for 2 h until completely dissolved. During the stirring process, tetraethyl orthosilicate is added and mixed evenly, and then coated on the surface of the substrate layer to form a chemical pre-coating layer, which is placed in an oven at 155 °C for curing for 15 s. Then, water, isopropyl alcohol, and carbon nanotubes are mixed according to the ratio and ultrasonically dispersed for 30 min, and then evenly coated on the surface of the chemical pre-coating layer to form an antistatic layer, which is placed in an oven at 140 °C for curing for 15 s to obtain the finished product. In the finished product, the thickness of the substrate layer is 50 μm, the thickness of the chemical pre-coating layer is 3 μm, and the thickness of the antistatic layer is 0.02 μm.

[0057] Comparative Example 5

[0058] In this comparative example, a technical solution of an alcohol-resistant antistatic film with pure water-dispersed carbon nanotubes is provided, and the substrate layer is a PET film.

[0059] Chemical pre-coating raw materials: 80% of polyvinyl alcohol with a molecular weight of 25000 Da, 15% of isobutyl acetate, and 5% of tetraethyl orthosilicate;

[0060] Antistatic layer raw materials: 80% of water and 20% of carbon nanotubes with a diameter of 2 nm.

[0061] Preparation method: Polyvinyl alcohol and isobutyl acetate are mixed according to the ratio and stirred at 60 °C for 2 h until completely dissolved. During the stirring process, tetraethyl orthosilicate is added and mixed evenly, and then coated on the surface of the substrate layer to form a chemical pre-coating layer, which is placed in an oven at 155 °C for curing for 15 s. Then, water and carbon nanotubes are mixed according to the ratio and ultrasonically dispersed for 30 min, and then evenly coated on the surface of the chemical pre-coating layer to form an antistatic layer, which is placed in an oven at 140 °C for curing for 15 s to obtain the finished product. In the finished product, the thickness of the substrate layer is 50 μm, the thickness of the chemical pre-coating layer is 3 μm, and the thickness of the antistatic layer is 0.02 μm.

[0062] The antistatic films prepared in the above different embodiments and comparative examples were respectively subjected to surface resistance and resistance tests after alcohol resistance test. The alcohol resistance test method includes soaking a non-woven fabric in ethanol, wetting the base more than the base but not dripping, and wiping the surface of the antistatic film with mechanical energy using the non-woven fabric. The wiping pressure is a 500g weight, the friction stroke is 10cm, the reciprocating speed is 30 times / min, the number of wiping is 50 times back and forth, and the surface resistance test is performed after standing for 5 minutes.

[0063] At the same time, the adhesion is evaluated. According to ISO 2409 standard, a hundred-grid test is performed, with a 1mm spacing between the blades of the cross-cutting device, a 6-blade knife, a transparent tape (3M 600, width 25mm), and a 10x magnifying glass. Use the cross-cutting device to draw 6*6 1mm2 squares on the coating surface, deep to the substrate, and quickly tear off the cross-cut area vertically. The grade judgment standard is:

[0064] 5B: No coating peeling off

[0065] 4B: Shedding area ≤ 5%

[0066] 3B: 5%-15% shedding area

[0067] 2B: Shedding area 15%-35%

[0068] 1B: Shedding area>35%

[0069] The damp heat aging test, according to ICE 60068-2-78 "Constant damp heat test", hang the sample in the damp heat box to avoid contact with the box wall. The temperature is 85℃, the humidity is 85%RH, and the duration is 500h. After the test, take out the sample and restore it in the environment of 23℃ / 50%RH for 24h, and test the surface resistance after aging.

[0070] For the reusability test, the same sample is wiped with alcohol multiple times (50 times each time) according to the alcohol resistance test method. After each cycle, the surface resistance is measured. 7 Ω, it is judged as failure and the number of cycles is recorded.

[0071] The test results are shown in the following table:

[0072]

[0073] It can be seen from the data of Comparative Example 1 that when the formula of the antistatic layer is the same, if the pre-coating is missing, the resistance value after alcohol resistance increases sharply, which may be caused by alcohol penetration causing the carbon nanotubes to fall off, and the adhesion of the hundred grid test is extremely low. After the comparative example 2 omits tetraethyl orthosilicate in the chemical pre-coating, the resistance value after alcohol resistance has a large increase, which may be due to the lack of cross-linked structure causing alcohol penetration, thereby reducing alcohol resistance. The hundred grid test shows that the adhesion is not as good as that of Example 1, which may be because the cross-linked structure in tetraethyl orthosilicate improves alcohol resistance and adhesion. Comparative Example 3 adopts the common polythiophene coating scheme on the market, and its resistance after alcohol resistance test completely fails, and the adhesion is also relatively poor. After the comparative example 4 adopts carbon nanotubes with a larger diameter, the initial resistance value is high, and the resistance value after the alcohol resistance test also rises, which may be due to uneven dispersion causing local failure. After isopropyl alcohol is omitted in comparative example 5, the resistance value increases, and the resistance further deteriorates after the alcohol resistance test, so the mixed solvent system of water / isopropyl alcohol is a necessary condition for the dispersion of carbon nanotubes.

[0074] In summary, alcohol resistance (resistance stable at 10 5 Ω), high adhesion (5B) and reusability (≥5 times). The lack of any technical feature will lead to a cliff-like drop in performance (the difference in comparison data is 3-8 orders of magnitude).

[0075] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A reusable alcohol-resistant antistatic film, comprising a substrate layer, a chemical pre-coating layer and an antistatic layer sequentially arranged on the substrate layer, characterized in that: The chemical pre-coating layer is composed of polyvinyl alcohol, isobutyl acetate and tetraethyl orthosilicate with molecular weights ranging from 20000Da to 30000Da.

2. The reusable alcohol-resistant antistatic film according to claim 1, characterized in that: Calculated by weight percentage, the chemical pre-coating layer consists of 75%-85% of polyvinyl alcohol with a molecular weight of 20000Da-30000Da, 10%-15% of isobutyl acetate and 5%-10% of tetraethyl orthosilicate.

3. The reusable alcohol-resistant antistatic film according to claim 1, characterized in that: The antistatic layer consists of water, isopropyl alcohol and carbon nanotubes.

4. The reusable alcohol-resistant antistatic film according to claim 3, characterized in that: Calculated by weight percentage, the antistatic layer consists of 40%-45% of water, 40%-45% of isopropyl alcohol and 10%-20% of carbon nanotubes.

5. The reusable alcohol-resistant antistatic film according to claim 4, characterized in that: The diameter of the carbon nanotubes is 1-3 nm.

6. The reusable alcohol-resistant antistatic film according to claim 1, characterized in that: The substrate layer is a PET film.

7. The reusable alcohol-resistant antistatic film according to claim 1, characterized in that: The thickness of the substrate layer is 50-75 μm.

8. The reusable alcohol-resistant antistatic film according to claim 1, characterized in that: The thickness of the chemical pre-coating is 3-5 μm.

9. The reusable alcohol-resistant antistatic film according to claim 1, characterized in that: The thickness of the antistatic layer is 0.02-0.03 μm.

10. The method for preparing the reusable alcohol-resistant antistatic film according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: polyvinyl alcohol and isobutyl acetate are mixed according to a proportion, ethyl orthosilicate is added during stirring, the mixture is evenly coated on the surface of a substrate layer to form a chemical pre-coating layer, the mixture is placed in an oven at 150-160°C for curing for 10-20s, water, isopropanol and carbon nanotubes are mixed according to a proportion, stirred and evenly coated on the surface of the chemical pre-coating layer to form an antistatic layer, the mixture is placed in an oven at 135-145°C for curing for 10-20s to obtain a finished product.